Causation of human ulcerative colitis: A lead from an animal model that mirrors human disease - William E W Roediger (JGH Open, 2019)
Most models of experimental colitis do not replicate human ulcerative colitis and do not help in defining the causation of human ulcerative colitis. Inducing pantothenic acid deficiency in pigs produces an ideal model in terms of extent, histology, and chronicity of human ulcerative colitis. Comparing metabolic changes in human ulcerative colitis with metabolic changes in experimental colitis in pigs provided a guide for the search of initiating factors of human ulcerative colitis. Observations showed that bacterial nitric oxide with bacterial hydrogen sulphide reproduced the metabolic changes of human ulcerative colitis. Decreasing colon‐produced nitric oxide and hydrogen sulphide by bacteria through diet and medication resulted in pronounced therapeutic improvement, both clinically and histologically, of human ulcerative colitis.